Effect of cerium oxide nanoparticles coating on the electrodes of benthic microbial fuel cell. Issue 2 (22nd January 2019) - Pushkar, Priyakant; Prakash, Om; Imran, Mohd.; Mungray, Alka A.; Kailasa, Suresh Kumar; Mungray, Arvind Kumar
ABSTRACT: Benthic microbial fuel cell is a power source for low-power devices. For enhancement of power, Cerium oxide (CeO2 ) nanoparticles (NPs) were coated on anode and cathode electrodes and compared separately. CeO2 NPs were synthesized by hydrothermal method and characterized by Dynamic light scattering. Polyvinylidene fluoride and graphite powder were used as a conductive matrix for binding CeO2 NPs. Coated electrodes were characterized by physical and electrochemical analysis. Maximum power densities generated by CeO2 coated cathode and anode were 60 and 43 mW/m 3 respectively; whereas conductive matrix only produced 14 mW/m 3 . Results demonstrated that CeO2 at cathode performed better than at anode. NPs show their effectiveness as an oxygen reduction reaction catalyst in the sea water.